Register analysis of language use in the Jakarta Post’s football news - Neiza Moulita (English Education Journal, 2021)
This research investigated the types of linguistic forms of English register and the meaning of register used in The Jakarta Post Football news. The linguistic forms that are investigated are specifically in content words and noun phrases. To obtain the data, documentation was used as the instrument. The data were analyzed using the model proposed by Elo and Kyangas (2007), it was found that there are two kinds of data in the form of content words, eight data of nouns, two verbs. In the form of the noun phrase, the researcher found two data in the category of attributive adjective and seven data of nouns in noun phrases. All of English registers found in The Jakarta Post’s football news have different meanings when compared with their conceptual meaning in the dictionary. The most dominant type of change in meaning is social meaning.